1994
DOI: 10.1007/bf02331615
|View full text |Cite
|
Sign up to set email alerts
|

Workplace surveillance for carpal tunnel syndrome using hand diagrams

Abstract: Four hundred and eleven workers from 4 different companies participated in a worksite screening program designed, in part, to estimate the prevalence of carpal tunnel syndrome (CTS). Each worker completed a discomfort survey and underwent limited nerve conduction testing of the median and ulnar sensory nerves in both wrists. The discomfort survey included a hand diagram which allowed subjects to shade in area(s) affected by numbness, burning, tingling, or pain. The discomfort survey also asked each worker to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 11 publications
2
44
0
1
Order By: Relevance
“…The questionnaire incorporated items from previous research on upper extremity disorders, including items previously shown to have good to excellent test-retest reliability [19,24,[28][29][30][31][32]. Follow-up questionnaires with similar questions to the baseline questionnaire were completed at approximately 6 months, 18 months, and 36 months after baseline testing.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The questionnaire incorporated items from previous research on upper extremity disorders, including items previously shown to have good to excellent test-retest reliability [19,24,[28][29][30][31][32]. Follow-up questionnaires with similar questions to the baseline questionnaire were completed at approximately 6 months, 18 months, and 36 months after baseline testing.…”
Section: Methodsmentioning
confidence: 99%
“…Three expert raters including two occupational medicine physicians and one occupational therapist independently scored each hand diagram following the scoring criteria described by Franzblau et al [24]. All raters had prior research and clinical experience addressing upper extremity problems.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations